Obstacles of Total Quality Assurance Management in Higher Education Schools: Field Study - Saeed Aladadi (University of Science and Technology, Yemen, 2014)
abstract:  The overall goal of this research is to identify the obstacles that prevent the application of TQM in institutions of higher education.  The previous studies have been reviewed.  Then, the field study has been made which include hypotheses and the results.  The third Section contains of summary of the results and the recommendations. A questionnaire is prepared that consist of two parts. The first part represents 38 element that limit the application of TQM in institutions of higher education,  while the second section deals with information from primary investigator. Research population have been identified four faculty members at King Khalid University, namely:  Faculty of Shariah and Fundamentals of Religion, Faculty of Humanities, Faculty of Business Administration and Finance, Faculty of Education. The total valid questionnaires for analysis is (204), where the percentage of responses suitable for analysis is (60%) of the total sample. The most important results from the field study are:  • The main obstacles facing the application of TQM in institutions of higher education are: • 1.     Weak understanding of the concept of lifelong learning. • 2.     Weak financial support for scientific research. • 3.     weak capacities of libraries. • 4.     Increase the teaching load. • There is a difference between the major groups of constraints according to the specialization. • There is difference in assessing the degree of importance of the regulatory constraints and community service according to the experience of a faculty members, while in the rest of the sides. There are some proposed a number of recommendations including: • promote a culture of quality. • should start the public and administrative services. • much attention to incentives for faculty. • interest in supporting scientific research. • select leadership that have experience in implementation of Total Quality Management.